Impact of COVID-19 on the Yemeni economy: How the drop in remittances affected economic sectors, food systems, and households - Elsabbagh, Dalia; Kurdi, Sikandra; Wiebelt, Manfred (International Food Policy Research Institute, 2021)
There has been an unprecedented decline in the flow of remittances to Yemen – a vital source of money for millions – as a result of the COVID-19 pandemic. A Social Accounting Matrix (SAM) multiplier model of Yemen’s economy was used to estimate the impact of lower remittances on economic sectors and employment, food systems, and household incomes.